1989
DOI: 10.1128/mcb.9.10.4467
|View full text |Cite
|
Sign up to set email alerts
|

Translation in Saccharomyces cerevisiae: initiation factor 4E-dependent cell-free system.

Abstract: The gene encoding translation initiation factor 4E (eIF-4E) from Saccharomyces cerevisiae was randomly mutagenized in vitro. The In eucaryotes, ribosomes initiate translation of mRNA by binding at or near the 5'-terminal cap structure. Bound ribosomes then scan the mRNA in the 5' to 3' direction to find the first AUG codon in optimal sequence context (for reviews, see references 11, 14, and 19). Presumably, this cap-dependent pathway represents the major translation initiation pathway in eucaryotes. More rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 30 publications
2
88
0
Order By: Relevance
“…It is unclear if p220 cleavage is responsible for the poliovirusinduced host-cell shut-off of protein synthesis or if another event is responsible for this phenomenon [6,7,26,27]. Thus, it was of interest to analyze the effects of 2A pr° expression on S. cerevisiae macromolecular synthesis, since the protein synthesis machinery of this organism is similar to that of mammalian cells [28] and some of the factors involved in translation in these systems are interchangeable [29].…”
Section: Effect Of 2a Pr° Expression On Yeast Macromolecularmentioning
confidence: 99%
“…It is unclear if p220 cleavage is responsible for the poliovirusinduced host-cell shut-off of protein synthesis or if another event is responsible for this phenomenon [6,7,26,27]. Thus, it was of interest to analyze the effects of 2A pr° expression on S. cerevisiae macromolecular synthesis, since the protein synthesis machinery of this organism is similar to that of mammalian cells [28] and some of the factors involved in translation in these systems are interchangeable [29].…”
Section: Effect Of 2a Pr° Expression On Yeast Macromolecularmentioning
confidence: 99%
“…The yeast strain T93C (Altmann et al, 1989), containing a chromosomal deletion of eIF4E and a plasmid with eIF4E under control of a Gal promoter (eIF4E::LEU2 ura3 trp1 leu2 [pGal1-eIF4E URA3]), was transformed with pG-1 vectors (with an added NcoI site N terminus to BamHI in the cloning region) containing Arabidopsis eIF4E constructs. pG-1 provides constitutive gene expression and a TRP1 marker (Schena et al, 1991).…”
Section: Yeast Complementation Of Eif4ementioning
confidence: 99%
“…The ability of Arabidopsis eIF4E proteins to complement deletion of the eIF4E gene in yeast. Complementation was tested by introducing pG-1 plasmids for constitutive expression of Arabidopsis eIF4E genes into a yeast strain (T93C; Altmann et al, 1989) with eIF4E under control of a GAL promoter. Serial dilutions of midlog phase yeast were plated in 10-fold serial dilutions on SCM-Trp plates containing 2% Gal (A) or 2% Glc (B) and incubated at 30˚C for 48 h. The experiment was performed in three biological replicates; representative results are shown.…”
Section: Eif4e1b and Eif4e1c Can Complement Eif4e Deletion In Yeastmentioning
confidence: 99%
“…Temperature-sensitive alleles of the CDC33 gene lead to a defect in translation initiation in vivo and an arrest in the G 1 phase of the cell cycle (8)(9)(10)(11). Recently, the analysis of deletion variants of eIF4E with reduced affinity for the 5Ј cap indicated that eIF4E mediates the selectivity of yeast ribosomes for capped mRNAs (12).…”
mentioning
confidence: 99%